2016
DOI: 10.3389/fphys.2016.00092
|View full text |Cite
|
Sign up to set email alerts
|

Acute Response of Circulating Vascular Regulating MicroRNAs during and after High-Intensity and High-Volume Cycling in Children

Abstract: Aim: The aim of the present study was to analyze the response of vascular circulating microRNAs (miRNAs; miR-16, miR-21, miR-126) and the VEGF mRNA following an acute bout of HIIT and HVT in children.Methods:Twelve healthy competitive young male cyclists (14.4 ± 0.8 years; 57.9 ± 9.4 ml·min−1·kg−1 peak oxygen uptake) performed one session of high intensity 4 × 4 min intervals (HIIT) at 90–95% peak power output (PPO), each interval separated by 3 min of active recovery, and one high volume session (HVT) consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 71 publications
2
30
0
Order By: Relevance
“…The study shows that exercise can increase vascular endothelial miR-126 levels. A study on children by Wahl and colleagues [37] showed that high-volume training (130 min at 55% peak power output) and sprint interval training (4 × 30 s all-out) was followed by a large increase in circulatory miR-126 compared to baseline. Their results suggest that exercise can also improve miR-126 levels in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that exercise can increase vascular endothelial miR-126 levels. A study on children by Wahl and colleagues [37] showed that high-volume training (130 min at 55% peak power output) and sprint interval training (4 × 30 s all-out) was followed by a large increase in circulatory miR-126 compared to baseline. Their results suggest that exercise can also improve miR-126 levels in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, substantial variations in the whole blood c-miRNAs patterns between endurance and strength athletes and various exercise protocols were reported and support the idea that c-miRNAs are well suited to monitor the overall status of an athlete and the adaptation of organism to exercise [117,118,119,120,121,122,123,124,125]. …”
Section: Discussionmentioning
confidence: 89%
“…A huge number of studies have been focused on their potential as biomarkers for various diseases, particularly for cancer. In a similar manner, physical exercise has been shown to be an activator of gene expression and miRNA levels that vary considerably depending on the mode of exercise [30,59,60,61,62,63,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,117,118,119,120,121,122,123,124,125]. Many studies revealed miRNAs to have a potential as markers of muscle function and exercise adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations